2008
DOI: 10.4314/tjpr.v7i2.14608
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to International Guidelines in the Management of Hypertension in a Tertiary Hospital in Nigeria

Abstract: Purpose:The role of physicians in the overall management of hypertension and their adherence to the JNC VII, WHO/ISH and ESH guidelines were examined in this study. Method: Case notes of hypertensive patients diagnosed between 1 January 2004 and 30 September 2005, in the Cardiology Clinic of University of Benin Teaching Hospital were retrieved for evaluation. They were assessed for adherence to the JNC VII, WHO/ISH and ESH guidelines, in the management of hypertension. Result: Five hundred and one case notes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 17 publications
6
33
3
Order By: Relevance
“…More than two third (73.5 %) of the total prescriptions written were in compliance with CPG 2008. This finding is in contrast to some of the previous studies conducted elsewhere and Malaysia [11,12] which have reported poor adherence to guidelines, but is in compliance with some studies which have reported good adherence to guidelines [13,14]. This fair level of adherence to the hypertension guidelines might be due to the model proposed by Piette and Kerr [15].…”
Section: Discussioncontrasting
confidence: 56%
“…More than two third (73.5 %) of the total prescriptions written were in compliance with CPG 2008. This finding is in contrast to some of the previous studies conducted elsewhere and Malaysia [11,12] which have reported poor adherence to guidelines, but is in compliance with some studies which have reported good adherence to guidelines [13,14]. This fair level of adherence to the hypertension guidelines might be due to the model proposed by Piette and Kerr [15].…”
Section: Discussioncontrasting
confidence: 56%
“…The closest in percentage of blood pressure control to that obtained in this study are 25.4% (Salako et al, 2002), and 29% (Etuk et al, 2008) [with the latter having a female percentage of 54.5%]. Females have been relatively less responsive to antihypertensive therapy (Odili et al, 2008) …”
Section: Bp Uncontrolled 65%supporting
confidence: 50%
“…9 Other earlier studies also confirmed CCBs as the most prescribed drug followed by ACEIs and ARB 10 or diuretics. 11 The slight shift from CCBs back to diuretics could observed in prescriptions. Indeed patients on diuretics in this study had a significantly better BP control than those on other drug classes.…”
Section: Discussionmentioning
confidence: 99%
“…The prescription pattern of antihypertensive drugs among physicians and BP control among sub-sets in Nigeria has been extensively studied [9][10][11] but no study has been exclusively carried out in recent times to assess the impact of individual antihypertensive drug class on BP control in a sizable hypertensive population. This study aims at evaluating the effect of individual antihypertensive drug class on BP control among patients with or without complications/co-morbidity attending a tertiary hospital in southwest Nigeria.…”
Section: Introductionmentioning
confidence: 99%